2019
DOI: 10.1016/j.ab.2019.04.022
|View full text |Cite
|
Sign up to set email alerts
|

CYP26A1 gene promoter is a useful tool for reporting RAR-mediated retinoid activity

Abstract: Of numerous genes regulated by retinoic acid (RA), CYP26A1 is the most inducible gene by RA. In this study, we have used a shortened construct form, E4, of the CYP26A1 gene promoter, in a promoter-less vector with either luciferase or red fluorescent protein (RFP) as the reporter gene and have tested its responses to retinoids in transfected HepG2 and HEK293T cells. The promoter responded linearly to a wide concentration range of RA in cells cotransfected with retinoic acid receptors. It also responded quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…According to these studies, the expression of CYP26C1 might be regulated by RA-linked transcription factors. Taimi et al showed that RA induces CYP26C1 expression in a HPK1a cell line, and Zolfaghari et al reported that RAR-mediated signaling induces the expression of CYP26A1 (one of the CYP26 family) [16,40]. These data suggest that hypomethylation of CYP26C1 might induce its expression and might decrease regional RA, which affects the occurrence of SVO.…”
Section: Discussionmentioning
confidence: 99%
“…According to these studies, the expression of CYP26C1 might be regulated by RA-linked transcription factors. Taimi et al showed that RA induces CYP26C1 expression in a HPK1a cell line, and Zolfaghari et al reported that RAR-mediated signaling induces the expression of CYP26A1 (one of the CYP26 family) [16,40]. These data suggest that hypomethylation of CYP26C1 might induce its expression and might decrease regional RA, which affects the occurrence of SVO.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting observation was the induction of mRNA for CYP26A1, the enzyme responsible for ATRA catabolism and a sensitive indicator of ATRA bioactivity activity (55,56), by ATRA in THP-1 cells that were also treated with IL-4. This is in contrast to ATRA-induced CYP26A1 expression that was significantly reduced in THP-1 cells that were also treated with LPS (15).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of full-length human RXR was studied in transiently transfected HEK293T cells using firefly luciferase reporter constructs for the RXR homodimer (DR1 response element, Addgene, Watertown, MA, plasmid #1015) and the RXR:RAR heterodimer (pGL3-RARE-luciferase, Addgene, plasmid #13458). The full-length human nuclear receptors were overexpressed using pSG5-hRXR and pcDNA3.1-hRAR (Addgene, plasmid #135397). pRL-SV40 (Promega) was cotransfected for normalization of transfection efficacy and to observe test compound toxicity.…”
Section: Methodsmentioning
confidence: 99%